I’dadu Mawad ‘Ilm Al-Dilalah Al-Mustamidah Min Al-Ayat Al-Qur’aniyyah Fiy Manzhur Al-Madkhol Al-Istiqraiy - Abdurrahman Ahmad Agil, Abdurrahman (Mahad Aly Al Fithrah, 2024)
This study aims to: (1) Knowing the description of Arabic semantic materials derived from the verses of the Qur'an from the point of view of the inductive approach at Dar Al-Lughah and Da'wah University (2) Knowing the effectiveness of semantic materials derived from the verses of the Qur'an from the point of view of the inductive approach to Dar Al-Lughah and Da'wah University students until they are able to do it. The approach used in this research is the Borg & Gall development approach which contains the following steps: initial study, product planning, product development, product certification, first modification, field trial, and model production. The data collection methods used are observation, interviews, questionnaires and tests.The results of the study are: (1) The education book was prepared based on the initial study and needs analysis conducted by researchers to find out the teaching problems. (2) The results of the study were: (1) The education book was prepared based on the initial study and needs analysis conducted by the researcher to find out the problems of teaching Arabic language at the university level in the course of Arabic Semantics derived from Quranic verses in the perspective of the inductive approach at Dar Al-Lughah and Dakwah Bangil University, East Java. (2) The results of the experts' approval and assessment of the validity of the educational book were stated with a very good assessment or 90%, after analysing the curriculum and determining educational topics and student requirements, as the average post-test result = 94.3750 is greater than the average pre-test result = 83.1250, this shows the use of textbooks is effective. In addition, the result of the